ELECTRICAL TEACHERS AND THEIR DIGITAL COMPETENCES IN RELATION TO TEACHING - SERAFIN, Cestmir (Journal of Technology and Information Education, 2023)
The didactic process is a complex process influenced by many circumstances, both external and internal, and this is of course no different in the didactics and teaching process of electrical engineering. However, with the increasing digitalization of education, this process is changing significantly. Digital technologies enable more efficient and effective learning by providing learners with access to a wide range of resources such as online lectures, videos and simulations, as well as tools such as various software tools, virtual laboratories, etc. Thus, the didactic process in electrical engineering is changing significantly and it is necessary to adapt not only the learning process of students, but especially the process of preparing future teachers. The use of digital technologies, virtual laboratories and automated systems means being able to create a much more effective multimedia creative learning environment. However, are teachers of vocational electrical subjects sufficiently equipped with digital competences to conduct teaching requiring these competences? The paper therefore deals with mapping these areas in the environment of selected secondary schools in the Olomouc region.
Keywords: Professional didactics; didactic process; electrical engineering; digital literacy; digital competence; professional competence; online tools; vocational Education.